Restorative Justice in Customary Criminal Law in Indonesia: A Legal and Sociological Study - Putu Ulandari Sri Lestari; I Made Sudharma (Jurnal Indonesia Sosial Sains, 2026)
Restorative justice has emerged as a critical response to the retributive paradigm in criminal justice systems, which often neglects victim recovery and social harmony. In Indonesia, this approach is not new but has long been embedded in customary criminal law as part of the living law, emphasizing deliberation, community involvement, and the restoration of social balance. This study aims to analyze the regulation of restorative justice in Indonesian positive law and to examine the urgency of reforming criminal procedural law through the integration of customary criminal law values. The research employs a normative legal method using statutory, conceptual, and historical approaches, supported by descriptive, argumentative, and evaluative analysis techniques. The findings reveal that although restorative justice has been recognized in several legal instruments, including Law Number 11 of 2012 concerning the Juvenile Criminal Justice System and various internal regulations of law enforcement agencies, its regulation remains fragmented, sectoral, and not yet fully integrated into the national criminal procedural system. Meanwhile, customary criminal law demonstrates strong paradigmatic alignment with restorative justice, particularly in terms of community participation and social restoration. The study concludes that reforming national criminal law by integrating restorative justice principles based on customary law is essential to bridge the gap between positive law and living law, thereby fostering a more responsive, humane, and substantively just criminal justice system aligned with Indonesia's socio-cultural values.